The Effect of Diabetes Mellitus on Dental Pulp Organ: A Review - Elgendy, Ahmed; Besher, Nour; Esayah, Suleiman (Libyan Journal of Dentistry, 2018)
Diabetes mellitus (DM) is a systemic disease that brings numerous pathophysiological in the human body and oral complications are largely known and studied. Changes that occur in the dental pulp are of importance for the dentists, considering regular procedures outcome. The defense systems and neural connections of the dental pulp will be destroyed and disorganized. In the present article the literature concerning on complication, effect of Diabetes Mellitus on pulp and reparative response of dental pulp was reviewed.